2016
DOI: 10.1039/c5dt01741f
|View full text |Cite
|
Sign up to set email alerts
|

Carbene insertion into a P–H bond: parent phosphinidene–carbene adducts from PH3 and bis(phosphinidene)mercury complexes

Abstract: PH3 reacts with the in situ generated N-heterocyclic carbene DippNHC* (DippNHC* = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) to give the phosphanyl-imidazolidine [(Dipp)NHC*-H]-[PH2]. Upon treatment with an ortho-quinone, [(Dipp)NHC*-H]-[PH2] is dehydrogenated to give the parent phosphinidene-carbene adduct (Dipp)NHC*[double bond, length as m-dash]PH. Alternative routes to [(Dipp)NHC*-H]-[PH2] and (Dipp)NHC*[double bond, length as m-dash]PH employ NaPH2 and (TMS)3P7 (TMS = trimethylsilyl), respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 33 publications
3
82
0
1
Order By: Relevance
“…The in situ generated carbene inserts into the P-H bond of PH 3 , giving rise to a phosphanyl-imidazolidine 2a, which can be subsequently dehydrogenated to the NHC=PH adduct 3a. [12] N is observed. Excess NHC=PH and M(CO) 6 were removed by washing with n-hexane, yielding the pentacarbonyl complexes as pale yellow powders in 65 to 82% yield.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…The in situ generated carbene inserts into the P-H bond of PH 3 , giving rise to a phosphanyl-imidazolidine 2a, which can be subsequently dehydrogenated to the NHC=PH adduct 3a. [12] N is observed. Excess NHC=PH and M(CO) 6 were removed by washing with n-hexane, yielding the pentacarbonyl complexes as pale yellow powders in 65 to 82% yield.…”
Section: Resultsmentioning
confidence: 78%
“…A comparison of the structural properties of the adducts 1a and 3a and the mercury complexes 5a and 5b revealed that the different electronic properties of the unsaturated versus saturated NHCs are not reflected in the structures. [12] In addition to these findings, here we describe group 6 pentacarbonyl parent phosphinidene complexes of the structure [( Dipp NHC=PH)M(CO) 5 ] (6a-c, M = Cr, Mo, W), in which the NHC=PH unit acts as a two-electron ligand. These complexes are easily accessible from the metal hexacarbonyls and the adduct 1a (Scheme 5).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Thecompounds 3-5 are new members of the family.Much of the intrigue in this type of phospha-alkene focuses on the "inversely polarized" nature of the phosphorus-carbon bond, [18] which has been considered to have three resonance forms,o ne with af ormal C=Pd ouble bond, az witterionic form with aC À Ps ingle bond, and at hird form with aC!P donor-acceptor interaction (Scheme 3). Thelatter two forms have been invoked to rationalize the fact that the 31 PNMR chemical shifts in carbene phosphinidenes occur much further upfield than in typical phospha-alkenes.I na greement with this trend, the 31 PNMR chemical shifts for 3-5 in [D 6 ]benzene are d = À59.1, À52.1, and À75.1 ppm, respectively.T he compounds 3 and 4 also fit the observed trend of long C-P distances in carbene phosphinidenes, [15,16] with the distances being 1.769(3) and 1.766(2) , respectively (see Figure S67 and Table S3;d iffraction-quality crystals of 5 could not be obtained).…”
Section: Methodsmentioning
confidence: 74%
“…Carbene phosphinidenes were first reported in 1997, [15] and recent studies have shown that these compounds, [16] and closely related systems, [17] are the subject of renewed interest. Thecompounds 3-5 are new members of the family.Much of the intrigue in this type of phospha-alkene focuses on the "inversely polarized" nature of the phosphorus-carbon bond, [18] which has been considered to have three resonance forms,o ne with af ormal C=Pd ouble bond, az witterionic form with aC À Ps ingle bond, and at hird form with aC!P donor-acceptor interaction (Scheme 3).…”
Section: Methodsmentioning
confidence: 99%